Pre-hospital emergency medical service response time phenomenon in Klang Valley: An answer for the society - Nurumal, Mohd. Said (Qualitative Research Association of Malaysia, 2017)
This qualitative descriptive study, underpinned by naturalistic inquiry, explored the prehospital emergency medical service response time in Klang Valley by providing an in-depth information of the phenomenon. In this study, various levels of health care personnel participated in focus group discussion and semi-structured interview. The staff members consisted of many levels of category from the lower ranks up to the higher level administrative officers. Content analysis was employed in analysing all data. Every one of the key informants was aware of the importance of making immediate responses to each ambulance call received. They shared their thoughts, experiences, and challenges in achieving the ideal response time in line with international recommendations. There were five categories of issues that emerged and challenges that arose from delays in response time, namely, 1) insufficient key information; 2) inconsistent information leading to delayed arrival of ambulance; 3) traffic condition causing delay in ambulance speed; 4) lack of resources contributing to an increase in workload; and, 5) unassertiveness in the attitude of members of staff. The findings have provided an answer to the society with regard to the current pre-hospital emergency medical service issues related to delay in the service delivered. Thus, policy makers and pre-hospital health care service providers should develop a strategic action plan by focusing on these findings to reduce the response time of ambulance call.